Therapeutic potency of curcumin on radiodermatitis: A systematic review - Hossein Abdeahad; Nikoo Saeedi; Afsane Bahrami; Abdulridha Mohammed Al-Asady; Saeide Mansoori; Amir Avan; Majid Khazaei; Elnaz Ghorbani; Mikhail Ryzhikov; Seyed Mahdi Hassanian (Mashhad University of Medical Sciences, 2024)
Objective: Radiodermatitis (RD) is a frequent adverse event of radiotherapy (RT).  Currently, there is no consensus and approved protocol for the treatment of RD. Curcumin (CUR) is a natural polyphenol obtained from turmeric and it has low intrinsic toxicity in humans. The aim of this systematic review was to explore the efficacy of CUR for prevention and treatment of RD.Materials and Methods: A systematic literature review was performed in the following online databases: Cochrane library, PubMed, Scopus, Web of Science, MEDLINE, and EMBASE. Among the 5 selected records, 3 had a randomized clinical trial (RCT)-design and the other had a pilot and controlled study designed. The included studies were performed on breast cancer (N=3), head and neck cancers (N=1) and different types of cancer (N=1).Results: Four of the studies reported that the application of curcumin in cancer patients undergoing radiotherapy is associated with decreased intensity of radiodermatitis. However, one study did not report any significant effect of CUR on radiodermatitis. This review provides substantial evidence which confirm the clinical value of CUR in cancer supportive care.Conclusion: Further prospective clinical trials in larger scales are warranted in order to determine the " supplemental form and dose of CUR" for RD prevention and treatment in patients receiving radiotherapy.